Amorphous Nitrogen Doped Carbon Films: A Novel Corrosion Resistant Coating Material1. Issue 5 (20th January 2014) - Zhu, Miao; Li, Xinming; Zhang, Zexia; Sun, Pengzhan; Zang, Xiaobei; Wang, Kunlin; Zhong, Minlin; Wu, Dehai; Zhu, Hongwei
Abstract : The challenge in developing a protection barrier from corrosion is to develop an economical yet efficient method for the coating material. Graphene has been deemed to be an ideal coating material for anti‐corrosion, yet its long‐term performance is disappointing due to galvanic corrosion. In an effort to address issues associated with graphene materials, we have developed an amorphous nitrogen doped carbon (a‐CN) film material exhibiting remarkable anti‐corrosion properties. The anti‐corrosion performance of this material appears to be superior to graphene because of its strong ion transportation resistance.